Application of Neuroscience on Architecture: The emergence of new trend of Neuroarchitecture - Maleki, Mohammad Reza; Bayzidi, Qader (Kurdistan Journal of Applied Research, 2017)
Understanding and knowing neuroscience and its sub-branches applications as well as their interconnections has a significant effect on science development. Simoltaneous application of neurology, psychology and architecture gain a new trend named “neuroarchitecture” or “basic nerve architecture”. This paper tries to consider this new trend through qualitative research and descriptive analysis method based on library information analysis. In this way current paper firstly deals with this subject background and neuroscience definition and then refers to entry areas of this subject to other sciences. Then basic information related to human brain and measurement instruments of neurology science will be presented. This paper deals with neuroscience on economy, education, aesthetics, and environment psychology in architecture areas. At the end concluding discussion will be presented through analytic method of neuroscience influence on architecture (neuroarchitecture) and its application method.